Cartier in the 20th century [accompanies the exhibition organized by and on view at the Denver Art Museum, 16 November 2014 - 15 March 2015] - Young-Sánchez, Margaret 1960- (Vendome [u.a.], 2014)
"Presents a meticulously selected overview of Cartier's contribution to 20th-century design and culture. Drawing extensively from the rich holdings of the Cartier Collection and Archive and the expertise of Cartier Heritage, it features not only a sumptuous array of rings, bracelets, necklace, and tiaras, but also cocktail and smoking accessories, mystery clocks, and lavish gifts exchanged by movie stars and maharajas, all created by Cartier's ateliers in Paris, London, and New York. ... Throughout, specially commissioned photographs of Cartier's legendary jewels and objects are accompanied by vintage photographs - drawn from the Condé Nast and Cartier archives - of royals, socialites, and Hollywood stars in their Cartier finery, including work by Steichen, Horst, Rawlings, Beaton, and Charbonneau."--Jacket